Comparative Effect of Soilless Substrates on Growth, Yield and Fruit Quality of Greenhouse Grown Cucumber (Cucumis Sativus L.). - Ameho, C.S. (University of Ghana, 2017)
Although the production of cucumber under greenhouse brings about higher yields and better fruit qualities, challenges of using soil medium coupled with high cost of cocopeat are some of the limiting factors. This prompted the investigation to compare the effect of soilless substrates on growth, yield and fruit quality of greenhouse grown cucumber (Cucumis sativus L.) at the University of Ghana Forest and Horticultural Crops Research Centre, Okumaning – Kade in the Eastern Region of Ghana from October 2016 to March 2017. A 2 x 6 factorial was laid out in Randomized Complete Block Design with three replications. The experiment consisted of two cucumber varieties (Kenzo F1 and Darina) and six substrates (Cocopeat (C), Palm Fibre (PF), Carbonated Rice Husk (CRH), Palm Fibre-Carbonated Rice Husk mix (PF + CRH) , Cocopeat-Palm Fibre mix (C + PF) and Soil (So). Data on physiochemical properties of substrates, growth indices, yield components and quality attributes were collected. Cost benefit analysis of the substrates were also determined. Analysis of Variance (ANOVA) was used to analyze the data using Genstat 12th edition statistical package. The results show that, the different soilless agricultural wastes investigated can be used to successfully produce cucumbers under greenhouse conditions. PF, C and PF+CRH results in good growth of greenhouse cucumber plants compared to So and CRH substrate. The soilless substrates that produced the best yield of greenhouse grown cucumber are PF (227.25 t/ha), C+PF (101.40 t/ha) and PF+CRH (88.05 t/ha). The soilless substrates that produced the best fruits quality in terms of TSS are C (4.42) and PF (4.18). Dry Matter (DM) was highest in C (5.63) followed by PF (5.33). The highest Moisture Content (MC) was recoded in PF (297.04), C + PF (194.82) and C (182.98). Revenue and profit recorded by Darina grown in PF was the highest (GHC 1,275,201.00 and 1,202,431.00). Based on the results from the work conducted, it is recommended that the optimum soilless substrate or their combination that cucumber growers in Ghana can use as an alternative growth media to soil in greenhouse are PF, C, PF + CRH and C+PF substrates.
Keywords: Effect of Soilless Substrates; Cucumis Sativus L.; Soilless Substrates on Growth; challenges of using soil medium